Roots of the quadratic equation is given by where quadratic equation is of form ax2 + bx + c = 0.
Substituting value of a = 1, b = – 3, c = – m(m + 3)
x = (m + 3), (-m)
Hence option B is correct.
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Glimpses of India39 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation